The Implementation of the Cotton Monopoly Policy in the Surkhandarya Oasis in 1946-1970 and its Results (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the years after World War II, large irrigation facilities began to be built in Uzbekistan. This process was carried out in accordance with the orders of the Central Committee of the All-Union Communist Party (Bolsheviks) and the Council of People's Commissars of the USSR issued in July 1945 and February 2, 1946. The period of construction of large irrigation networks has begun in Surkhandarya region.